Pengaruh Kualitas Audit Dan Komite Audit Terhadap Kecurangan Laporan Keuangan (Studi Empiris Pada Perusahaan Manufaktur Sektor Barang Konsumsi Primer Yang Terdaftar Di Bursa Efek Indonesia Tahun 2020-2023) - Luthfiyyah, Alya (Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2024)
The purpose of this study was to determine the effect of audit quality and audit committee on financial statement fraud in manufacturing companies in the primary consumer goods sector listed on the Indonesian stock exchange in 2020-2023. The study used 240 sample data from 60 companies for 4 years of research. . The research results show that audit quality has a negative and significant effect on financial statement fraud. Good audit quality can reduce financial statement fraud. Furthermore, the audit committee has no effect and not significant on financial statement fraud, a poor audit committee will increase financial statement fraud.